Biosynthesis of Silver Nanoparticles Using Vinca Rosea Leaf Extract and its Biological Applications Against Human Pathogens - Lalsangi, Dayanand; Hanagodimath, S. M.; Jadhav, Mangesh S.; Tangod, Vadiraj B.; Vanti, Gulamnabi (The Nucleus, 2023)
We report green synthesis of silver nanoparticles (Ag-NPs) for biological applications against human pathogens. Vinca rosea leaf extract was used to swiftly generate silver nanoparticles which were characterized by different techniques. The structural and optical properties of the synthesized nanoparticles were measured using UV-visible spectrophotometer, X-ray diffractometer, scanning electron microscope (SEM) coupled with energy-dispersive X-ray spectroscopy (EDS), and transmission electron microscopy (TEM). The surface morphology of the nanoparticles was found to be of spherical shape with crystalline phase. Further, the antibacterial activity, anti-cancer, anti-diabetic, anti-microbial, anti-oxidant properties, anti-helminthic, anti-ulcer, hypotensive, anti-diarrheal, wound healing, and hypolipidemic activity of Vinca rosea reduced silver nanoparticles reveal that they are highly effective agents for gram-positive and gram-negative bacteria. The green silver nanoparticles have shown significant antibacterial potential against different bacterial strains.